EXPLORING INDONESIAN GENERATION Z MOTIVATION IN ACCESSING SOCIAL MEDIA LIVE STREAM SHOPPERTAINMENT - Tania, Syaifa (Master of Communication Science Program, Universitas Diponegoro, 2024)
Livestream shoppertainment has become the most promising type of social commerce in Indonesia. The main idea of livestream shoppertainment combines shopping experience and entertainment values to become an additional point enabling audience to receive product information and entertainment at the same time. This research aims to explore generation Z motivation in accessing livestream shoppertainment in social media as they tend to favor digitally seamless shopping experience more than other generations. Uses and gratification is used as the main framework. The data is collected through survey by distributing 404 online questionnaires towards generation Z in Indonesia. According to the result, audience motivation in accessing livestream shoppertainment is based on the fulfillment of utilitarian, hedonic, and social gratifications. The duality of utilitarian gratifications towards other types enables livestream shoppertainment is seen as a marketing communication option that is not necessarily to get done the task of purchasing journey, but also to gain any forms of hedonic and social benefits. Fulfilling the needs of utilitarian, hedonic, and social gratifications become important approach to reach generation Z as an audience as well as a consumer in social media platform.